21.2k views
0 votes
−2x+2y=12 and -2x+8y=-12−2x+8y=−12

User HatemTmi
by
4.5k points

1 Answer

3 votes

Answer:

(- 10, - 4 )

Explanation:

Given the 2 equations

- 2x + 2y = 12 → (1)

- 2x + 8y = - 12 → (2)

Multiply (2) by - 1

2x - 8y = 12 → (3)

Add (1) and (3) term by term to eliminate the x- term, that is

- 6y = 24 ( divide both sides by - 6 )

y = - 4

Substitute y = - 4 into either of the 2 equations and solve for x

Substituting into (1)

- 2x + 2(- 4) = 12

- 2x - 8 = 12 ( add 8 to both sides )

- 2x = 20 ( divide both sides by - 2 )

x = - 10

solution is (- 10, - 4 )

User Chabislav
by
4.7k points